Turning waste into wealth: a conceptual design of limonene production plant from waste rubber tyre - Tan, Kok Wei; Sheng, Brian Quan Sia; Tey, Ker Yee; Kon, Tat Wah; Lam, Jia En; Tan, Peng Chee; Noraini Mohd, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Limonene production represents a compelling opportunity in the global market, given its competitive landscape dominated by a few key players who control nearly half of the industrial-grade limonene market. Due to the high polyisoprene content in vehicle tyres, along with the rising number of waste rubber tyres, the production of limonene by pyrolysis of tyres may represent a future trend to turn waste into wealth. Hence, a conceptual plant design was carried out to determine the feasibility of limonene production from waste rubber tyres in Malaysia. This feasibility study involved Aspen Plus simulation and illustrated the main processes using Process Flow Diagram (PFD), Piping and Instrumentation Diagram (P&ID), and comprehensive stream table integrating material and energy balances. The desired product, which is limonene, was produced by the gas-solid pyrolysis within a conical spouted bed reactor (CSBR) in an inert atmosphere of non-oxidizing, achieving limonene of 98% purity. Besides, process optimization via pinch analysis has been performed to recover 223.84 kWh of energy using heat integration, resulting in 62.06% of energy saving. From the economic analysis conducted, the total capital investment is RM12.9 million and the annual revenue is RM124.7 million with an annual limonene production of 543.1 tons. The financial analysis demonstrated a robust return on investment (ROI) of 303%, a simple payback period of 0.33 years and ta Net Present Value (NPV) of RM 432.2 million.